Analisis Yuridis Terhadap Sanksi bagi Pelaku Usaha yang Tidak Mendaftarkan Surat Tanda Pendaftaran Waralaba - Ambarwati, Melyani Dwi; Permatasari, Pita (Postulat, 2024)
The rapid development of franchise businesses has had an impact on economic growth in Indonesia. Franchising is a promising business and is popular with the public. In this case, the franchise agreement must have an STPW, but many business owners still do not have one. Therefore, the franchise case which fulfills the unlawful act in the Surabaya court decision number 837/Pdt.G/2021/Pn.Sby is caused by not being in accordance with Government Regulation Number 42 of 2007 concerning Franchising and Minister of Trade Regulation Number 31/M-DAG/PER /8/2008 which causes losses to franchise recipients. In the agreement, Hanashobu does not have a Franchise Registration Certificate. This research is normative research using descriptive analysis methods based on court decree number 837/Pdt.G/2021/Pn.Sby. The results of this research can be concluded as legal protection is given after the dispute is resolved in a court decision. Thus, the franchiser, in this case Hanashobu Japanese Noodle Bar, is responsible for returning all costs for losses to the franchisee and the agreement is deemed null and void.